1.). Solve this quadratic formula:
-3x^2 + 16 + 12 =====> Solution -3x^2 + 28
Let's simplify step-by-step.
−3x^2 + 16 + 12
Combine Like Terms:
= −3x^2 + 16 + 12
= (−3x^2) + (16 + 12)
= −3x^2 + 28
Answer:
= −3x^2 + 28
Answer =======> -3x^2 + 28
2). Solve the Quadratic Formula:
-3x^2 + 16x + 12 =====> - ( x - 6 ) ( 3x + 2 )
Steps:
-3x^2 + 16x + 12
Factor out Common Term -1:
- (3x^2 - 16x - 12 )
Factor:
3x^2 - 16x - 12: ( x - 6 ) ( 3x + 2 )
x^1 =======> -2/3
x^2 =======> 6
Answer =========> - (x - 6 ) ( 3x + 2 )
Hope that helps!!!! : )